Statistical Physics : an entropic approach - Ford, Ian, 1962- (2013)
"This undergraduate textbook provides students with a statistical mechanical foundation to the classical laws of thermodynamics through a comprehensive treatment of the basics of classical thermodynamics, equilibrium statistical mechanics, irreversible thermodynamics, and statistical mechanics of non-equilibrium phenomena. The concept of entropy is studied starting from the ideal gas law, known to every undergraduate. By considering various thermodynamic processes, it then explores the concept's generality. An accessible style enables undergraduates to easily follow the presentation without much prior knowledge. The focus on entropy distinguishes the book from many other treatments of this subject"--
"Focuses from the beginning on entropy as the important quantity and introduces it thoroughly in the context of classical thermodynamics"--
Includes index.
Keywords: Statistical thermodynamics -- Textbooks; SCIENCE / Mechanics / Dynamics / Thermodynamics